2014
DOI: 10.1016/j.immuni.2014.10.019
|View full text |Cite
|
Sign up to set email alerts
|

STING-Dependent Cytosolic DNA Sensing Promotes Radiation-Induced Type I Interferon-Dependent Antitumor Immunity in Immunogenic Tumors

Abstract: SUMMARY Ionizing radiation-mediated tumor regression depends on type I interferon (IFN) and the adaptive immune response, but the several pathways control I IFN induction. Here, we demonstrate that adaptor protein STING, but not MyD88, is required for type I IFN-dependent antitumor effects of radiation. In dendritic cells (DCs), STING was required for IFN-β induction in response to irradiated-tumor cells. The cytosolic DNA sensor cyclic GMP-AMP (cGAMP) synthase (cGAS) mediated sensing of irradiated-tumor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
1,516
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,639 publications
(1,560 citation statements)
references
References 43 publications
36
1,516
3
5
Order By: Relevance
“…6,1517 Investigations in different mouse tumor models revealed that radiotherapy-induced anti-tumor immune reactions, which are essentially dependent on type-I interferons (produced by the cyclic GMP-AMP synthase (cGAS)/stimulator of interferon genes (STING) axis), APCs, and cytotoxic CD8 + T cells, are exclusively stimulated by high single doses (10–20 Gy). 1823 On the contrary, a recent study suggests that 3 × 8 Gy may be optimal. 24 Clinically, abscopal tumor lesion regression remains rare, most likely because comparable super-hypofractionated protocols (fractions of >5 Gy) are rarely used in the radiotherapeutic routine.…”
Section: Introductionmentioning
confidence: 99%
“…6,1517 Investigations in different mouse tumor models revealed that radiotherapy-induced anti-tumor immune reactions, which are essentially dependent on type-I interferons (produced by the cyclic GMP-AMP synthase (cGAS)/stimulator of interferon genes (STING) axis), APCs, and cytotoxic CD8 + T cells, are exclusively stimulated by high single doses (10–20 Gy). 1823 On the contrary, a recent study suggests that 3 × 8 Gy may be optimal. 24 Clinically, abscopal tumor lesion regression remains rare, most likely because comparable super-hypofractionated protocols (fractions of >5 Gy) are rarely used in the radiotherapeutic routine.…”
Section: Introductionmentioning
confidence: 99%
“…STAT1 phosphorylation can be elicited following activation of the DNA dependent pattern recognition receptor (PRR) cGAS and its downstream mediators STING and IRF3, which serve to transcriptionally activate type I interferon 816 . CRISPR-Cas9 knockout of either cytosolic cGAS or STING reduced activation of downstream IRF3 target genes ISG54, ISG56 and the NF-κB target CCL5 post-IR (Fig 3a and Extended data 3a) 17, 18 .…”
mentioning
confidence: 99%
“…By contrast, inhibition of HMGB1 or knockout of downstream TLR4 signaling components has no effect on subcutaneous colon cancer cells following radiotherapy [99]. In this model, radiotherapy response is dependent on type I IFN signaling in dendritic cells and the adaptor protein STING [98,99]. Whether the discrepancy between the roles of myeloid cells in these studies is caused by the differences in tumor model, or by the differences in radiotherapy dose and schedule remains to be investigated.…”
Section: Innate Immune Cellsmentioning
confidence: 86%
“…For example, HMGB1-sensing TLR4 + dendritic cells are required for radiotherapy efficacy in subcutaneous thymomas [58]. By contrast, inhibition of HMGB1 or knockout of downstream TLR4 signaling components has no effect on subcutaneous colon cancer cells following radiotherapy [99]. In this model, radiotherapy response is dependent on type I IFN signaling in dendritic cells and the adaptor protein STING [98,99].…”
Section: Innate Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation